"Crossroads" of Culture and Education as a Methodological Basis for Modern Pedagogy Content Formation - Smolinska, Olesia; Dzyubynska, Khrystyna (Journal of Vasyl Stefanyk Precarpathian National University, 2016)
The article deals with various aspects of culture and education combination in order to seek methodological basis for the formation of new pedagogy content. Particularly, the following aspects which combine culture and education are analyzed: ontological unity of man and society, the common evolution of culture and spirituality and, namely, the dialectical character of connection between phenomena of culture and education. The authors, who base on philosophical and pedagogical sources focus on the thesis about the necessity of developing fundamental approaches to the development of educational content in general. However, researchers consider the contradiction that exists between expediency of rapid contents transformation and their culture stipulated gravitation - the key issue of the current state of affairs. Authors find the solution to this problem in common conceptual and dynamic characteristics of culture and education, which form a specific unity - cultural and educational space. This phenomenon, in its turn, has the ability to generate culture appropriate contents of both modern education and pedagogy